Epilepsy risk among survivors of intensive care unit hospitalization for sepsis. (20th October 2020) - Antaya, Tresah C.; Allen, Britney N.; Richard, Lucie; Shariff, Salimah Z.; Saposnik, Gustavo; Burneo, Jorge G.
Abstract : Objective: To determine whether survivors of intensive care unit (ICU) hospitalizations with sepsis experience higher epilepsy risk than survivors of ICU hospitalizations without sepsis, and to identify sepsis survivors at highest risk. Methods: We used linked, administrative health care databases to conduct a population-based, retrospective matched cohort study of adult Ontario residents discharged from an ICU between January 1, 2010, and December 31, 2015, identified using the Discharge Abstract Database. We used propensity scores to match patients who experienced sepsis during their index ICU hospitalization with up to 4 patients who did not experience sepsis. We applied marginal Cox proportional hazards regression to estimate the risk of epilepsy within 2 years following the index ICU hospitalization. Among sepsis survivors, Cox proportional hazards regression was used to identify factors associated with epilepsy. Results: A total of 143, 892 patients were included, 32, 252 (22.4%) of whom were exposed. Sepsis survivors were at significantly higher epilepsy risk (hazard ratio [HR] 1.44, 95% confidence interval [CI] 1.15–1.80). The risk of epilepsy marginally decreased with increasing age (HR 0.97, 95% CI 0.96–0.99); patients with chronic kidney disease (HR 2.25, 95% CI 1.48–3.43) were at highest risk. Conclusions: In this real-world analysis, sepsis survivors, particularly those who are younger and have chronic kidney disease, are at significantly higher epilepsy risk. These findings indicate that sepsis may be an unrecognized epilepsy risk factor.